Pengaruh Motivasi Kerja, Disiplin Kerja dan Beban Kerja Terhadap Kepuasan Kerja Guru dan Karyawan SMP Negeri 6 Jombang - Sa’adah, Lailatus; Taqiyuddin, Akhmad; Agustin , Wilujeng Ayu (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2024)
The aim of this research is to discuss work motivation, work discipline and workload on job satisfaction of teachers and employees of SMP Negeri 6 Jombang. The method used is the associative method, which is research carried out to determine whether there is a relationship or influence between two or more variables. This research was conducted at SMP Negeri 6 Jombang. The data collection technique used was questionnaire data collection. The sample used consisted of 55 respondents using non-probability sampling techniques, primary data sources using observation, documentation and distributing questionnaires directly then processed using SPSS for Windows version 26. The results of research and data processing show that work motivation has a positive effect on job satisfaction, work discipline has a negative effect on job satisfaction and workload has a positive effect on job satisfaction.